“Remote” landslide-related hazards and their consideration for dams design - Strom, Alexander; Zhirkevich, Anatoly (Italian journal of engineering geology and environment, 2013)
<span data-sheets-value="{"1":2,"2":"The 1963 Vajont disaster highlighted the importance of slopes stability analysis not only directly at the dam sites but also in the reservoir areas to ensure hydraulic projects safety. However, catastrophic collapse of huge rock/soil mass into reservoir does not exhaust negative effects of landslides that must be taken into consideration in the course of dams design. Severe consequences might result from river channel landslide damming both downstream from the dam site and far upstream from the reservoir. Their potential effects are exemplified by several case studies from the Central Asia region. Measures aimed to mitigate negative effects of such extreme events are discussed."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">The 1963 Vajont disaster highlighted the importance of slopes stability analysis not only directly at the dam sites but also in the reservoir areas to ensure hydraulic projects safety. However, catastrophic collapse of huge rock/soil mass into reservoir does not exhaust negative effects of landslides that must be taken into consideration in the course of dams design. Severe consequences might result from river channel landslide damming both downstream from the dam site and far upstream from the reservoir. Their potential effects are exemplified by several case studies from the Central Asia region. Measures aimed to mitigate negative effects of such extreme events are discussed.